DIAGNOSTIC ACCURACY OF AMNIOTIC FLUID INDEX IN DETERMINATION OF POOR APGAR SCORE AMONG FEMALES WITH POST-TERM PREGNANCY - Dr. Sumbal Altaf; Dr Sumaira Hafeez; Dr Bazla Younas; Dr Zainab Iftikhar; Dr Zahra Anwar; Dr Shumaila Khalil (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
This study aimed to evaluate the diagnostic accuracy of amniotic fluid index to predict the poor Apgar score in females with postdate pregnancy in a tertiary care hospital taking poor Apgar score at birth as the gold standard. A cross-sectional study was conducted in the Obstetrics and Gynecology Department of Jinnah Hospital, Lahore from December 2023 to December 2024. A total of 300 pregnant women aged 20-40 years with